Study of the surface pressure fluctuations generated by waves and turbulence in the nocturnal boundary layer during SABLES2006 field campaign - Yagüe, Carlos; Viana, Samuel; Maqueda, Gregorio; Morales, Gema (Física de la Tierra, 2008)
Small-scale, short-period surface pressure fluctuations are perhaps one of the less studied features in the atmospheric boundary layer (ABL). These perturbations can be produced by fast turbulent motions and also by the propagation of internal-gravity waves generated close to the ground when stability is present. In this work nocturnal data from SABLES2006 field campaign is analyzed in order to characterize the wave-like structures detected during the most stable periods of the campaign by means of a wavelet analysis. In addition, we will relate the spectral characteristics of surface pressure fluctuations to the turbulent and stability parameters measured from tower data.